2021
DOI: 10.3912/ojin.vol26no03man06
|View full text |Cite
|
Sign up to set email alerts
|

Calling Nursing Informatics Leaders: Opportunities for Personal and Professional Growth

Abstract: New and emerging technologies in healthcare incorporate big data and artificial intelligence analytics change every day. With the continued integration of technology into healthcare, we need more Nursing Informatics (NI) leaders. To identify actionable steps emerging NI leaders can take to mature, we conducted a website scan of eight professional organizations and two interviews with nurse leaders who have experience in those organizations. This article discusses nursing informatics and nursing leadership, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, this article looks at supporting the NI leadership pipeline from an organizational and current leader perspective. Additional results from this study from the emerging NI leader perspective can be found in Backonja and colleagues 14 …”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Therefore, this article looks at supporting the NI leadership pipeline from an organizational and current leader perspective. Additional results from this study from the emerging NI leader perspective can be found in Backonja and colleagues 14 …”
mentioning
confidence: 56%
“…Additional results from this study from the emerging NI leader perspective can be found in Backonja and colleagues. 14…”
mentioning
confidence: 99%